Potensi Supply dan Demand Wisata Edukasi Kelola Sampah Anorganik di Desa Cibanteng: Potential Educational Tourism Supply and Demand in Cibanteng Village for Managing Inorganic Waste - Rahmawati; Ekayani, Meti; Pramudita, Danang; Rahmawati, Rahmawati (Indonesian Journal of Agricultural Resource and Environmental Economics, 2023)
The waste issue persists in Indonesia, primarily characterized by household-generated plastic waste dominating the waste composition. Educational tourism plays a pivotal role in encouraging and educating the public on environmental conservation. Cibanteng Village in Bogor Regency exhibits potential for the development of educational tourism, fostering sustainable green practices within the village. This research aims to identify the components of tourism green classes, analyze their social, economic, and environmental impacts, and assess the potential implementation of green class tourism. The methodology incorporates descriptive analysis, the Contingent Valuation Method (CVM), Likert scale, and a literature review. The study reveals an alignment between supply and demand for implementing edutourism green classes, showcasing visitor Willingness to Pay (WTP) lower than the Willingness to Accept (WTA) of the manager. Prospective trial tourists exhibit a higher WTP compared to prospective non-trial tourists. The economic, social, and environmental impacts of edutourism green classes indicate positive outcomes, including income generation from tourism, waste reduction, and potential sustainability impacts on green activities. In essence, the edutourism green class shows significant potential for implementation in Cibanteng Village.